The treatment approach to pediatric non-rhabdomyosarcoma soft tissue sarcomas: a critical review from the INternational Soft Tissue SaRcoma ConsorTium - Ferrari, Andrea; Orbach, Daniel; Sparber-Sauer, Monika; Walterhouse, David O.; Pajtler, Kristian Wilfried; Meyer, William H.; Spunt, Sheri L.; Weiss, Aaron R. (European journal of cancer, 2022)
The current article focuses on non-rhabdomyosarcoma soft tissue sarcoma (NRSTS), the heterogeneous group of mesenchymal tumours different from rhabdomyosarcoma that may affect children and adolescents, with clinical behaviour varying from relatively benign to highly malignant. This review represents the effort of the international scientific paediatric community within the context of the INternational Soft Tissue SaRcoma ConsorTium (INSTRuCT), a project founded by the leadership of three large cooperative groups - Children's Oncology Group, Cooperative Weichteilsarkom Studiengruppe and European paediatric Soft tissue sarcoma Study Group - with the main goal to pool expertise and resources on a broader international level in order to improve knowledge of soft tissue sarcomas of children, adolescents and young adults. This article describes the current standard treatment approach in NRSTS, with a focus on the controversies and challenges in the management of these tumours. Developing research projects and clinical protocols for NRSTS has always been challenging, supporting the need to develop international integrated prospective dedicated programs, including paediatric NRSTS experts together with the adult sarcoma community. INSTRuCT provides a unique mechanism to increase international collaboration by agreeing on a common language, developing consensus standards to guide diagnosis and treatment, comparing clinical trial results across cooperative groups, and through a shared data dictionary providing answers to questions that can only be addressed by a larger data set.